Factors Influencing Stress Management Among TVET MARA Students During Practical Training - BINTI SAPAN, MURNI; Muhammad Suhaimi Sulong (Research and Innovation in Technical and Vocational Education and Training, 2025)
Students in Technical and Vocational Education and Training (TVET) institutions are often exposed to significant levels of stress during their practical training due to heavy workloads, complex technical tasks, and demanding industrial expectations. If unmanaged, this stress may negatively impact their mental well-being, academic performance, and competency development. Therefore, this study aims to identify the level of stress and the stress management strategies among students in TVET MARA institutions in Batu Pahat during their practical and hands-on training. The study focuses on stress factors related to skills-based training, including workload, time constraints, pressure to achieve specific competencies, and the requirement to train in real industrial environments. A quantitative research design was employed using survey questionnaires distributed to first- and second-year students. The data were analyzed using descriptive and inferential statistics, including t-tests, Pearson correlation, and Mann-Whitney tests. The findings revealed that students experienced a moderate level of stress. The most dominant stress management strategies were emotion-focused approaches, such as rest, spiritual practices, and seeking social support. The study also found a significant relationship between stress levels and the strategies used, as well as differences in stress and management strategies based on gender and year of study. This study highlights the importance of effective mental health support and early intervention to ensure student well-being and the effectiveness of the teaching and learning process. The implementation of a holistic institutional-level stress management programmed is recommended as a proactive measure to support students in navigating the challenges of practical training.